Theoretical perspectives on public entrepreneurship. Issue 6 (3rd June 2019) - Liddle, Joyce; McElwee, Gerard
Abstract : Purpose: The interest in entrepreneurship in the public sector is recognized as an emergent phenomenon in the field of entrepreneurship. Existing theoretical work is limited in helping understand how entrepreneurship in public agencies occurs. The paper aims to discuss this issue. Design/methodology/approach: This is a conceptual paper which develops the literature. Findings: Building on the work of Klein et al. (2010) this paper contributes to theoretical development by providing an overview of public sector entrepreneurship (PSE). Although, there are similar features shared by private and PSE, it is proposed that there are significant differences between them, particularly in that public sector enterprise can be seen as entrepreneurship without entrepreneurs. Research limitations/implications: As a conceptual paper on PSE the literature is predominantly UK based. Practical implications: This paper brings entrepreneurship from the periphery to the core of the theoretical debates, as it is an under-researched area. Moreover, theoretical development has implications for policy and practice as existing research is disparate. Originality/value: The paper considers how entrepreneurship and enterprise in the public sector is formulated. The significance of the paper is to highlight the importance of public entrepreneurs in working alongside a multitude of stakeholders to deal with numerous global and internal environment forces ethically amongst on-going budgetary and fiscal constraints. The contribution is the highlighting of the difficulties and concerns when uniting the discourse of market-based entrepreneurship and the discourse of public sector service provision.